2014
DOI: 10.1515/joepi-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy with Electrical Status Epilepticus in Slow Wave Sleep – a review with an emphasis on regional (perisylvian) aspects

Abstract: SUMMARYAim. The aim of this article is to review criticaly the Electrical Status Epilepticus in Slow Sleep (ESES) phenomenon from a neurophysiological mechanisms aspect as well as terminological and classification issues. Methods. The review includes all the relevant papers published during the last 43 years on the subject of ESES and Continous Spike -Wave in Sleep (CSWS).These papers were identified in various large databases via the internet. Rewiev and remarks. ESES/CSWS phenomena can be held as a common fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 76 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…1% of cases. Looking into the increasing focus on these conditions in the literature [4,14,[48][49][50][51][52][53][54][55][56][57][58][59][60] and the estimations of involved professionals, it is likely that ESES/LKS is much more prevalent with an even higher heuristic significance.…”
Section: The Interrelations Of Spectrum Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…1% of cases. Looking into the increasing focus on these conditions in the literature [4,14,[48][49][50][51][52][53][54][55][56][57][58][59][60] and the estimations of involved professionals, it is likely that ESES/LKS is much more prevalent with an even higher heuristic significance.…”
Section: The Interrelations Of Spectrum Conditionsmentioning
confidence: 99%
“…A source of contradictions is the interpretation of the electrical patterns of ESES. ESES is considered a synchronous bilateral spike-wave pattern by several authors, but abundant data support the uni-hemispheric, focal/regional localization of discharges [4]. The newly described variants increase the terminological and taxonomic confusion (see in Appendix A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, BECTS, PS, atypical BECTS, LKS and ESES share a similar perisylvian location of IEDs, an important increase in IEDs during sleep, a deterioration of language and executive functions of various intensities as well as common genetic mutations (De Negri, 1997;Doose et al, 2001;Halász et al, 2005;Panayiotopoulos et al, 2008;Lemke et al, 2013;Lesca et al, 2013;Turner et al, 2015). Sleep-related IED activation in ESES is henceforth thought to represent an extreme exaggeration of what is seen in BECTS during sleep, both in space and synchronicity (De Negri, 1997;Halasz et al, 2014). Earlier EEG studies based on visual sleep stage scoring in patients with BECTS had identified slow wave sleep has a potent activator of IEDs (Beaumanoir et al, 1974;Dalla Bernardina et al, 1982;Clemens and Majoros, 1987), with the descending slope of the cycles having the greatest activating properties (Clemens and Majoros, 1987).…”
Section: Activation and Modulation Of Ieds During Sleep In Esesmentioning
confidence: 99%
“…Furthermore, due to the diversity of the epileptiform discharges, which are mainly focal/regional discharges or bilateral spike-waves, 2 he raises doubt about the existence of unitary mechanism of ESES and suggests that most of the discharges might reflect a more confined regional network. 3 A better understanding of the morphology and localization of the epileptiform discharges during ESES is an important issue. However, as noted by Dr. Hal asz, there are only few studies analyzing the potential fields of ESES discharges.…”
mentioning
confidence: 99%